(untitled) (Al-Academy, 2024)
Turkey is one of the most important countries in the Islamic world, which is famous for its historical architecture, including the Topkapi Palace, where it occupied an important place in the history of the Ottoman era, leaving its mark with an ancient cultural heritage, reflecting in it architectural styles, in addition to the diversity of arts in general, such as glass, ivory, metal, wood, textiles, and ceramic artifacts in general. Special, where it enjoyed great prosperity, through which it revealed ceramic artistic productions that expressed a homogeneous vision due to the marriage between artistic and functional aesthetic performance ((Özlü, Nilay: From imperial palace to museum: The Topkapı Palace during the long Nineteenth Centurt, Turkey, 2018, pp) ), that the Topkapi Palace with its artistic ceramic productions of pots and tiles and the diversity of its decorative styles came as a result of the sultans’ love for art and their passion for collecting artifacts and beautifying their buildings, and this is what was studied in the current research (a study of ceramic artistic employment in the Sultans’ Topkapi palace as an example) through the study and analysis of some The selected ceramic art models in the palace. The study consisted of four chapters. The methodological and included framework dealt with the problem represented by the following questions: What is the mechanism of ceramic art recruitment in Topkapi Sultans Palace. The importance of the research, the aim of the research, and the limits of the research. The second section dealt with the artistic presentation of the holdings of the palace, while the third topic focused on the study of ceramics in Topkapi Palace. And the indicators of the theoretical framework, while the third chapter included research procedures, defining its community and its sample, and closing the research with a presentation of the results of the research and conclusions, and an index of sources and reference.